2007
DOI: 10.1016/j.ijsolstr.2007.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Rupture mechanisms in combined tension and shear—Micromechanics

Abstract: A micromechanics model based on the theoretical framework of plastic localization into a band introduced by Rice is developed. The model consists of a planar band with a square array of equally sized cells, with a spherical void located in the centre of each cell. The periodic arrangement of the cells allows the study of a single unit cell for which fully periodic boundary conditions are applied. The micromechanics model is applied to analyze failure by ductile rupture in experiments on double notched tube spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
98
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(108 citation statements)
references
References 34 publications
1
98
0
1
Order By: Relevance
“…The third invariant (related to the Lode angle) of the deviatoric stress has been considered in constitutive models to predict localization (Brünig et al, 2000) and fracture (Bai and Wierzbicki, 2008). Barsoum and Faleskog (2007) showed that the strain localization decreases when passing from tension to shear, and the softening rates decreases when increasing the Lode parameter. Gao et al (2009) demonstrated that the Lode parameter has an important effect on the strain at coalescence and this effect is lower at high triaxiality, coinciding with the previous results from Zhang et al (2001).…”
Section: Shear Extensionmentioning
confidence: 99%
“…The third invariant (related to the Lode angle) of the deviatoric stress has been considered in constitutive models to predict localization (Brünig et al, 2000) and fracture (Bai and Wierzbicki, 2008). Barsoum and Faleskog (2007) showed that the strain localization decreases when passing from tension to shear, and the softening rates decreases when increasing the Lode parameter. Gao et al (2009) demonstrated that the Lode parameter has an important effect on the strain at coalescence and this effect is lower at high triaxiality, coinciding with the previous results from Zhang et al (2001).…”
Section: Shear Extensionmentioning
confidence: 99%
“…Moreover, with the variations of materials, specimen geometries, boundary conditions and measurement techniques in the literature, different conclusions can be obtained on the characteristics of ductile failure. For instance, the ductile failure strain under low stress triaxiality conditions was found to exhibit a nonmonotonic dependence to the stress triaxiality by Bai and Wierzbicki (2010) and Barsoum and Faleskog (2007), while a monotonic dependence was found by Haltom et al (2013), Ghahremaninezhad and Ravi-Chandar (2013) and Papasidero et al (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies [12][13][14][15][16][17][18][19][20][21] have shown that the Lode angle, associated with the third invariant of the deviatoric stress tensor, is an essential parameter in ductile fracture. It characterizes the effect of the stress state on plastic flow and the ductile rupture of the material.…”
Section: Introductionmentioning
confidence: 99%